Minorités linguistiques autochtones des Alpes italiennes - Ernst Steinicke; Judith Walder; Roland Löffler; Michael Beismann (Revue de Géographie Alpine)
More than any other area in Western Europe, the Alps, especially the Italian Alps, are home to great ethno-cultural diversity: there, no less than seven autochthonous linguistic minorities coexist side by side with the respective official majority. Now being considered an important cultural heritage by the state as well as by the regions, new legislation offers protection to all ‘linguistic-historic minorities’ in Italy. Our study shows, however, that it is quite difficult to maintain such groups, since it is largely unknown where exactly the minority areas are situated. Based on that, local actor groups in various communities take advantage of this lack of knowledge and declare themselves minority territories although they show no linguistic varieties. An important objective of this project is therefore to present a cartographic representation of this linguistic diversity. Subsequently, the contribution discusses case studies of distinct ethno-linguistic self-awareness. Even though with Law No. 482 a first important step was taken to preserve the linguistic minorities, their progressive decline by territorial and numerical criteria cannot be denied. Today, besides unfavorable bio-demographic factors and “diffuse ethnicity,” other causes are current demographic processes. In this framework the amenity migrants, those new immigrants who have discovered the mountains as a new, desirable settlement space, play a decisive role by reinforcing the assimilation process.